Pengaruh Kearifan Lokal dalam Pengembangan Islam di Indonesia - Tikasari, Putri Ariyatna (Maliki Interdisciplinary Journal, 2025)
Local wisdom plays an important role in the process of spreading and developing Islam in Indonesia. Through harmonious interaction between Islamic teachings and local culture, Islam can be widely accepted by people from diverse social and cultural backgrounds. This research aims to analyze the influence of local wisdom on the development of Islam in Indonesia, particularly in shaping moderate, inclusive, and contextual Islamic character. The method used is qualitative with a literature study approach, gathering data from various sources such as books, scientific journals, and historical documents. The study results indicate that integrating local wisdom with Islamic values creates a harmonious adaptation between religion and tradition, enriches national culture, and strengthens social cohesion within a diverse society. Indonesia’s experience in developing Islam based on local wisdom can serve as a model for the peaceful and adaptive application of Islamic teachings amidst the cultural diversity of the modern world.